2019
DOI: 10.1039/c9ra03209f
|View full text |Cite
|
Sign up to set email alerts
|

Heteropoly acid-encapsulated metal–organic framework as a stable and highly efficient nanocatalyst for esterification reaction

Abstract: Silicotungstic acid (HSiW) encapsulated UiO-66 nanocatalyst have been successfully synthesized by one-pot synthesis strategy and used as a stable and highly efficient catalyst for esterification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 44 publications
(32 reference statements)
2
36
0
Order By: Relevance
“…Examples are PTA@MIL-53 (Fe) (Nikseresht et al, 2017), AILs/HPW/UiO-66-2COOH (Xie and Wan, 2019b), and ZnFe 2 O 4 /MIL-100(Fe) (Hu et al, 2019). Meanwhile, our previous studies showed the esterification of oleic acid or lauric acid with methanol over silicotungstic acid and nickel salts of Keggin-type heteropolyacids encapsulated into metal-organic framework (UiO-66) hybrid nanocatalysts that had excellent activity and reusability (Zhang et al, 2019b(Zhang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are PTA@MIL-53 (Fe) (Nikseresht et al, 2017), AILs/HPW/UiO-66-2COOH (Xie and Wan, 2019b), and ZnFe 2 O 4 /MIL-100(Fe) (Hu et al, 2019). Meanwhile, our previous studies showed the esterification of oleic acid or lauric acid with methanol over silicotungstic acid and nickel salts of Keggin-type heteropolyacids encapsulated into metal-organic framework (UiO-66) hybrid nanocatalysts that had excellent activity and reusability (Zhang et al, 2019b(Zhang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of POM/CFO/MIL-101(Cr) dosage. For the optimization of the initial adsorbent dose, a series of experiments was accomplished with varied POM/CFO/MIL-101(Cr) adsorbent amounts (10,20,30, and 40 mg) at pH 6 in 30 mL of 100 mg L À1 MB solutions ( Fig. 5d) and 50 mg L À1 RhB solutions (Fig.…”
Section: Dye Adsorption Studymentioning
confidence: 99%
“…28 POMbased metal-organic frameworks (POM@MOFs) are a class of crystalline porous materials integrating the advantages of polyoxometalates (POMs) and metal-organic frameworks (MOFs), and are widely used as catalysts and adsorbents. [29][30][31] When the POM@MOFs materials are used in the elds of adsorption, adsorbate molecules can diffuse into the cages of MOF, and the POM polyanions previously encapsulated in the cages can act as additional active sites for adsorption. The introduction of POM clusters into MOF cages is an effective strategy for producing materials with enhanced adsorption performances.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to be compatible with diesel engines without requiring special modifications and will result to no negative impacts to operating performance of the engines [5]. Biodiesel is produced by the transesterification of virtually any triglyceride feedstock and this includes oil-bearing crops, animal fats, and algal lipids [6,7]. In the process, the triglycerides react with alcohols in the presence of a catalyst to produce fatty acid alkyl esters (known as biodiesel).…”
Section: Introductionmentioning
confidence: 99%